Analysis of the category content and form of Azur & Asmar workpiece: reflections on ethnic-racial relations in and out of school (Práxis Educativa, 2022)
This study had as its objects the literary work Azur & Asmar, written and illustrated by Michel Ocelot, 2007 edition, and the film Azur & Asmar: The Prince’s Quest, directed and animated by the same author, in 2006. The objective of the research was to understand the relationship of the category of content and form present in the works as possibility for expanding the reader’s competence and worldview about human diversity. For the development of the work, the bibliographic research methodology with a critical-dialectical approach was used. The analysis allowed to state that reading and understanding the elements of the content and form of the works are essential for the global comprehension of the textual meanings and an important educational process capable of promoting reflection and racial equality.Keywords: Literary reading. Content and form. Ethnic-racial education.